2010
DOI: 10.1002/bip.21506
|View full text |Cite
|
Sign up to set email alerts
|

Substrate screening of protein kinases: Detection methods and combinatorial peptide libraries

Abstract: The study of protein kinases has become a matter of great importance in the development of new drugs for the treatment of diseases, including cancer and inflammation. Substrate screening is the first step in the fundamental investigation of protein kinases and the development of inhibitors for use in drug discovery. Towards this goal, various studies have been reported regarding the development of phospho-peptide detection methods and the screening of phosphorylated peptide sites by protein kinases. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 126 publications
(148 reference statements)
0
28
0
Order By: Relevance
“…Commercial phosphotyrosine antibodies typically recognize short mammalian phosphopeptides; in some cases even five amino acids were previously shown to be sufficient for recognition [35], [50], [55], [56]. To systematically analyze the recognition capabilities of phosphorylated CagA EPIYA-motifs by α-phosphotyrosine antibodies we first synthesized a series of peptides derived from the EPIYA-A motif exhibiting the phosphotyrosine residue in the middle +/− five, four, three or two flanking amino acids, including the STEPIYAKVNK (11-mer), TEPIYAKVN (9-mer), EPIYAKV (7-mer) and PIYAK (5-mer) sequences as indicated (Figure 1B, top).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Commercial phosphotyrosine antibodies typically recognize short mammalian phosphopeptides; in some cases even five amino acids were previously shown to be sufficient for recognition [35], [50], [55], [56]. To systematically analyze the recognition capabilities of phosphorylated CagA EPIYA-motifs by α-phosphotyrosine antibodies we first synthesized a series of peptides derived from the EPIYA-A motif exhibiting the phosphotyrosine residue in the middle +/− five, four, three or two flanking amino acids, including the STEPIYAKVNK (11-mer), TEPIYAKVN (9-mer), EPIYAKV (7-mer) and PIYAK (5-mer) sequences as indicated (Figure 1B, top).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the α-phosphotyrosine antibodies were originally developed for mammalian proteins and typically recognize short amino acid stretches containing the phosphorylated tyrosine residue, including synthetic phospho-peptides [35], [50], [55], [56]. We therefore proposed that phospho-peptides derived from the CagA EPIYA-motifs would be useful for studying the recognition capabilities by seven commercial antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8]15 (ii) Alternatively, high throughput methods, such as phage display or mRNA display, can be used to find rare binding proteins amidst large combinatorial libraries of nonbinding sequences. [16][17][18] The hydrophobic core of a protein is generally well packed, with few cavities. Previous studies showed that creation of new cavities in a protein core can produce binding sites where small molecules can bind.…”
Section: Introductionmentioning
confidence: 99%
“…The randomized peptide library immobilized on beads was also coupled with chemical modification via beta-elimination [52] or incorporation of thiophosphoryl group [53] to detect phosphorylated substrate peptides and applied to profiling of other protein kinases.…”
Section: Random Peptide Librariesmentioning
confidence: 99%